An Integrative Character Education Model in English Language Learning for High School Students - suhrah; Muhammad Akbar; Askahar (Universitas Pendidikan Ganesha, 2025)
The development of character education requires teachers to be able to effectively integrate moral values and virtues into the learning process. However, implementing the right strategies in English language learning remains a challenge in many schools. This study aims to analyze teachers' strategies in integrating character values into English language learning. A qualitative approach with a case study method was used to explore in depth the teaching practices of six English teachers. Data were collected through analysis of lesson plans, classroom observations, and in-depth interviews, then analyzed using thematic analysis techniques. The results show that teachers apply character integration in a planned, contextual, and sustainable manner through problem-based learning, open discussions, role-play, community projects, and value reflection. Conceptually, this study confirms that value-based integrative strategies can strengthen language proficiency while shaping students' social and moral character. The conclusion of the study shows that the integration of character education in English language learning requires a transformation of the pedagogical paradigm from merely teaching language to shaping the values and identities of students. Implicitly, the results of this study can be used as a reference in the development of teacher training and character education policies in secondary schools.